Biosynthesis of ZnO Nanoparticles Using : Characterization and Nutritive Significance for Promoting Plant Growth in L - Sumera Sabir; Muhammad Asif Zahoor; Muhammad Waseem; Muhammad Hussnain Siddique; Muhammad Shafique; Muhammad Imran; Sumreen Hayat; Imran Riaz Malik; Saima Muzammil (SAGE Publishing, 2020)
Nano-fertilizer(s), an emerging field of agriculture, is alternate option for enhancement of plant growth replacing the synthetic fertilizers. Zinc oxide nanoparticles (ZnO NPs) can be used as the zinc source for plants. The present investigation was carried out to assess the role of ZnO NPs in growth promotion of maize plants. Biosynthesized ZnO NPs (using Bacillus sp) were characterized using Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), X-ray diffraction (XRD) and Zeta potential. Different concentrations of ZnO NPs (2, 4, 8, 16 mg/L) were explored in pot culture experiment. Size of ZnO NPs ranged between 16 and 20 nm. A significant increase in growth parameters like shoot length (61.7%), root length (56.9%) and significantly higher level of protein was observed in the treated plants. The overall pattern for growth biomarkers including the protein contents was maximum at 8 mg/L of ZnO NPs. It was observed that application of biosynthesized ZnO NPs has improved majority of growth biomarkers including plant growth parameters, protein contents and leaf area. Therefore, biosynthesized ZnO NPs could be considered as an alternate source of nutrient in Zn deficient soils for promoting the modern agriculture.